Korelasi Motivasi Dengan Prestasi Belajar Ilmu Pengetahuan Sosial Siswa di Mtsn 12 Jombang - Ainun Jariyah (Jurnal Ilmu Pendidikan dan Sosial, 2023)
Humans as the most noble creatures by themselves will not become noble just like that, but someone must foster, lead and direct them. This action is a learning process in an educational institution. Learning is a process of changing behavior that occurs in a single situation, even in a vacuum. This learning situation is characterized by the motives set and accepted by students. The purpose of this study was to determine the motivational condition of class IX students at MTsN 12 Jombang on social science learning achievement. In this study there were two variables, namely motivation which is the independent variable or (X). while Social Science learning achievement is the dependent variable (Y), with a questionnaire on 77 respondents from class IX MTsN 12 Jombang, using descriptive data analysis of percentage and product moment correlation. And from the results of this study by looking at the product moment r table value, it turns out that with a df of 75 at a significant level of 1%, an r table of 0.217 is obtained, while at a significant level of 5%, we get an r table of 0.283. greater than the price of r table. Both at a significant level of 5% (0.38 > 0.217) or at a significant level of 1% ) 0.38 > 0.283), it means that there is a moderate positive effect. The results of this study indicate that the higher the student's learning motivation, the higher the learning achievement in Islamic religious subjects, and the lower the student's learning motivation, the lower the achievement in Social Sciences subjects.